Force majeure impact on citizen science: Perspective from an EU funded project [version 2; peer review: 1 approved, 2 approved with reservations] - Huma Shah; J. Vallverdu; M. Pocs; Tiberius Ignat; M. Hinsenkamp; Maayan Zhitomirsky-geffet (Open Research Europe)
Background Management of citizen science engagement during a force majeure needs very careful consideration in order not to lose precious time. This paper serves as a guide for pro-action in the event of another virus-enforced stay-at-home, movement-control order and presents necessary changes undertaken by an international collaboration during a once-in-a-hundred years’ pandemic that reduced face-to-face public interactions. Overcoming challenges imposed under force majeure conditions, a citizen science project funded under the EU Horizon2020 research and innovation scheme SwafS15-2019, required re-thinking provision of experiential learning through volunteering screen time. Methods Mitigation measures, to limit the handicap of moving to online working reducing potential for learning through synchronous live engagement, included creation of an interactive multilingual informal five-step learning resource (CSI-COP MOOC: ‘Your Right to Privacy Online’), adapting Greenpeace’s ‘Big Plastic Count’ to an online ‘Big Cookie Count’ event, as well as webinars organised by project partners in their local language, Newsletters, provided opportunities for the general public to gain vital knowledge about protecting personal data and preserving online privacy. Results Over one-hundred and ninety members of the public who completed CSI-COP’s MOOC with a certificate, participated in one-to-one online ‘walk through’ training sessions in local languages joined the project, through GDPR-compliant written informed consent, as citizen scientists. The acquisition of practical skills by these individuals enabled investigations of websites they visited and apps they used to record third-party cookies or third-party requests for personal data. Conclusions The effective reorganisation of CSI-COP activities to online, then hybrid once COVID-19 restrictions were lifted, ensured the expected deliverables were produced. Citizen scientists’ contributions realised a searchable Repository of investigated websites and apps, a Taxonomy of tracking cookies, two policy briefs on improving monitoring of GDPR compliance, and Guidelines to address the ‘legitimate interest’ principle used by third parties to gather personal data online.